Gender-sensitive social protection: A critical component of the COVID-19 response in low- and middle-income countries - Hidrobo, Melissa; Kumar, Neha; Palermo, Tia; Peterman, Amber; Roy, Shalini (International Food Policy Research Institute, 2020)
As social protection programs and systems adapt to mitigate against the COVID-19 crisis, gender considerations are likely to be overlooked in an urgent effort to save lives and provide critical economic support. Yet, past research and learning indicates that small adaptations to make program design and implementation more gender-sensitive may result in overall and equality-related gains. We summarize some of these considerations for LMICs across five areas: 1) Adapting existing schemes and social protection modality choice, 2) targeting, 3) benefit level and frequency, 4) delivery mechanisms and operational features, and 5) complementary programming. It is our hope that COVID-19 will be an opportunity to address, and not exacerbate, pre-existing gender inequalities and lay the groundwork for more gender-sensitive social protection programming in LMICs beyond the crisis, building toward the wellbeing of societies as a whole.